Investigating mathematics teachers’ beliefs about the nature of mathematics and their impact on classroom practices - Maphutha, Beauty Kgaladi (My University, 2012)
This study investigated Mathematics teachers’ beliefs about the nature of Mathematics and their impact on classroom practices. It was conducted in a public semi-urban school in the Capricorn District-Limpopo Province. It was a case study targeting two FET teachers with teaching experiences of 15 years or more. The central research questions addressed in this study are, namely: What are Mathematics teachers’ beliefs about the nature of Mathematics? And, what is the relationship between teachers’ beliefs and their classroom practices? Data were collected through pre-observation interviews, classroom observation and through post observation interviews. Pre-observation interviews were conducted once before the participants were observed. I was a complete observer during my colleagues’ lessons. Interviews and observations data were analysed using categorisation and interpretation of data in terms of common themes and synthesis into an overall portrait of the case. Each case study teacher’s data were analysed individually (that is within-case analysis) first and thereafter cross-case analysis was done in order to compare the two case studies.
Thesis (M.ED. (Mathematics Education)) -- University of Limpopo, 2012
Keywords: Mathematics teaching; Teachers' beliefs; Mathematics -- Study and teaching; Mathematics teachers